Risk Factors of Low Vision in Children - Tiur Dianawati; Liena Sofiana (International Journal of Public Health Science (IJPHS), 2015)
Low vision and blindness is a vision disorder that becomes an important issue with regard to a person's independence. According to data owned by the World Health Organization in 2011, the number of blind people in the world reached 39 million, 246 million for low vision and 285 million for blindness. The purpose of this study was to know the incidence of risk factors in children with low vision in Low Vision Service Center Pertuni Yogyakarta, Indonesia. This study was an observational analytic study employed cross sectional design. The subject participated in this study was 139 children. Data were analyzed using correlation analysis. The instrument used was check list. There were relationships between the sex with low vision (p = 0.028, RR = 1.308), there was no relationship between regular eye checkup with low vision incidence (p = 0.801, RR = 1.054). There was relationship between the use of vision aids with low vision (p = 0.000, RR = 0.640), there was a relationship between the cataract with low vision (p = 0.000, RR = 1.472), there was a correlation between the refractive disorderwith low vision (p = 0.000, RR = 0.625).There should be an awareness of health behaviours in the use of vision aids as needed and balanced diet with sufficient physical activity and regular.